Plasmonic and phononic properties of epitaxial conductive transition metal nitrides. (1st July 2020) - Gioti, M; Arvanitidis, J; Christofilos, D; Chaudhuri, K; Zorba, T; Abadias, G; Gall, D; Shalaev, V M; Boltasseva, A; Patsalas, P
Abstract: The dielectric function, reflectivity and Raman spectra of several epitaxial transition metal nitride films (TiN, ZrN, NbN, TaN, MoN, WN) on MgO substrates are reported. Apart from WN, the studied films exhibit a negative real part of the dielectric function, and thus may sustain plasmonic resonances with varying quality factors and at diverse spectral regions. Epitaxial TiN and ZrN outperform the rest of the studied nitrides in terms of the plasmonic figures of merit. TiN and ZrN colloidal nanoparticles in water and ethanol are predicted to support localized surface plasmon resonances at 596 and 496 nm, respectively. Surprisingly, the reported epitaxial films are not superior to their previously reported polycrystalline counterparts due to the existence of point defects (mostly metal vacancies for group Vb nitrides and both metal and nitrogen vacancies for group VIb nitrides) as revealed by the Raman spectra. Raman spectroscopy emerges as a sensitive tool for the detection of point defects in epitaxial transition metal nitrides via the recording of the otherwise forbidden first order acoustic modes. The role of the various structural defects in the optical and plasmonic performance of the films is discussed. Unlike the traditional plasmonic metals (Ag and Au), the point defects are revealed to be of paramount importance for the optical response of the reported alternative plasmonic materials.